The Working Group On Urban Sparrows 6th International meeting in Breda (Netherlands) 2019:20 21 March (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The 6th meeting was held in Breda (the Netherlands)on the 20th and 21th of march 2019, as a cooperation between the city of Breda (Van Eekelen Rombout), Bird Protection Netherland (Koojmans Jip Louwe & Vreugdenhil Stefan) and ABLLOvzw/ groep Terec UGent (De Laet Jenny). Here I present the abstracts of the talks on the 21th of March 2019.
Keywords: wróblowe; ornitologia